Co-existent Presence of Alopecia Areata in Siblings: A Rare Presentation - Mohanty, Sandip (Medknow Publications & Media Pvt Ltd, 2014)
Alopecia areata (AA) is a T cell mediated autoimmune disease with multifactorial etiology resulting in partial and total nonscarring alopecia. We hereby report a case of two brothers (aged 7 and 5 years) presenting with coincidental AA over scalp which is a rare presentation.